Beta diversity of urban floras among European and non‐European cities. Issue 7 (13th March 2014) - La Sorte, Frank A.; Aronson, Myla F. J.; Williams, Nicholas S. G.; Celesti‐Grapow, Laura; Cilliers, Sarel; Clarkson, Bruce D.; Dolan, Rebecca W.; Hipp, Andrew; Klotz, Stefan; Kühn, Ingolf; Pyšek, Petr; Siebert, Stefan; et al.
Abstract Aim Cities represent an ideal study system for assessing how intensive land‐use change and biotic interchange have altered beta diversity at broad geographic extents. Here we test the hypothesis that floras in cities located in disparate regions of the globe are being homogenized by species classified as invasive (naturalized species that have spread over a large area) or as a European archaeophyte (species introduced into Europe before ad 1500 from the Mediterranean Basin). We also test the prediction that the global influences of European activities (colonization, agriculture, commerce) have supported this outcome. Location One hundred and ten cities world‐wide. Methods We examined the richness and composition of urban floras among European (n = 85) and non‐European cities (n = 25) for species classified as native or non‐native, or further classified as European archaeophyte or invasive. We modelled how geographic, climatic and anthropogenic factors were related to compositional similarity between European and non‐European cities. Results We found that most plants in the cities we examined, particularly non‐European cities, were native and unique to each city. Non‐native species were similarly unique, but occurred in much lower proportions relative to natives. Although European archaeophytes and invasive species also occurred in lower proportions, they had similar compositions among cities. European archaeophytes were most prevalent in European cities, but were most similar among non‐European cities. Contrasting European and non‐European cities, geography and climate were most relevant for native and invasive species, whereas climate and agriculture were most relevant for European archaeophytes. Main conclusions Cities in disparate regions of the globe retain regionally distinct native and non‐native plant assemblages, while invasive species, and especially European archaeophytes, were associated with lower beta diversity among cities. These findings suggest that intensive land‐use change and biotic interchange, shaped through European influences, have had a world‐wide effect on the beta diversity of urban plant assemblages.